Wettable powder formulations of Metarhizium anisopliae (Metchnikoff) sorokin and their effectiveness against Bemisia tabaci Gennadius and Aphis gossypii Glover - Latiff, Norhelina (2019)
Sap sucking insect Bemisia tabaci Gennadius (Hemiptera: Aleyrodidae) and Aphis gossypii Glover (Hemiptera: Aphididae) have become important pests infesting economic important crops and worsened by their resistance to a multiple classes of chemical pesticide and among them are organophospates, pyrethroids and neonicotinoid. These have prompted potential of utilizing biological control as an alternative to chemical insecticide. Of these, Entomopathogenic fungi (EPF) are the most suitable due to their ability infecting through the cuticle and displaying a great prospective for controlling sap-sucking pest. One of these EPF is Metarhizium anisopliae. There is little information on the effect of M. anisopliae on the sap-sucking insect in Malaysia. The objectives of this study were to screen the most virulent isolate of M. anisopliae against B. tabaci and A. gossypii, prepare the wettable powder (WP) and evaluate the effect of UV and storage on the formulations, and assess the WP formulations effectiveness in the field. Five isolates of M. anisopliae (PR1, GT2, TFFH3, GJ4 and HSAH5) were highly pathogenic against first instar of B. tabaci and A. gossypii and the two most superior were PR1 and GJ4. The B. tabaci was invulnerable on brinjal than chilli and vice versa on A. gossypii. The LC50’s of PR1 isolate against B. tabaci and A. gossypii were lower than GJ4 isolate on both brinjal and chilli host plant. Both PR1 and GJ4 isolates were highly infective to all developmental stages of B. tabaci and A. gossypii; with the first instar was prone to fungal disease than other life stage decreasing through the next stages. In the preparation of the wettable powder (WP) formulation, the compatibility of inert ingredients on conidial viability was never lower than 80% and most was between 90–96% in all tests. The ingredients of the WP formulation comprised of active ingredient of fungal conidia and inert ingredients. The inert ingredients consisted of diluent (glycerin, distilled water), three components of surfactant system (combination of three of the following: sodium naphthalene sulphonates, sodium lignosulfonate, kaolin, silica powder, skimmed milk powder), UV protectant (lignin, skimmed milk powder, molasses) and additive (sodium glutamate, sodium alginate). The 22 prepared WPs from both isolates gave germination ranging from 65.0 to 93.6%. Wettable powder-based kaolin and WP-based skimmed milk powder enhanced the UV tolerance of conidia and gave significantly better germination than WP based silica powder. The WPs were able to maintain conidia viability up to four months storage at temperature 4℃, 16℃ and 25℃. Nevertheless, at 30℃ the viability was only maintain for a maximum of four weeks. In the small-scale field trial, selected WP of PR1 and GJ4 based kaolin were more effective compared to unformulated isolates conidia and untreated control. These formulations also gave significantly better yield compared to unformulated isolates and untreated control. M. anisopliae isolates PR1 and GJ4 effectively control sap sucking insect both in laboratory and in the field against all stages of B. tabaci and A. gossypii and able to improve the yield.